What do dental students expect from oral and maxillofacial surgery externships?. Issue 11 (15th July 2022) - Smith, Natalie R.; Bradshaw, Shenan M.; Roser, Steven M.; Abramowicz, Shelly
Abstract: Introduction: Limited information exists on the goals and expectations of dental students from oral and maxillofacial surgery (OMS) externships. This information is valuable to OMS residency programs. Dental students use externships to gain insight into various OMS residency programs.  The purpose of this project was to answer the following question: "what do dental students expect from OMS externships?" Purpose: The aim of this study was to report the expectations of dental students from OMS externships. Materials and Methods: This cross‐sectional study took place from June 2015 to September 2019. Every student completing an Emory OMS externship completed an anonymous survey. The survey consisted of questions regarding (1) demographics, (2) previous OMS experience, and (3) open‐ended questions regarding expectations and sources of anxiety. Answers were grouped into categories with similar answers. Descriptive statistics summarized data. Results: Of 116 externs who completed the survey, the majority were males ( n  = 80, 68.9%) with a mean age of 25 (range 21–30) years old in the 3rd/4th year of dental school. Most had previous OMS experience ( n  = 103, 89.6%) and plan to apply to OMS residency ( n  = 104, 90.4%). Most externs hoped to learn about life as a resident and the scope and culture of the program. Externs expressed the highest level of anxiety regarding their own experience and/or knowledge level. Conclusions: This project demonstrated that during the externship, externs expect to gain insight into the daily activities, scope, and culture of the OMS program they are visiting.